2010
DOI: 10.4061/2010/495015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bovine Tuberculosis in Abattoirs of the Littoral and Western Highland Regions of Cameroon: A Cause for Public Health Concern

Abstract: Bovine tuberculosis (BTB) is widespread but poorly controlled in Africa and M. bovis is posing threats to human health. The risk of cattle handlers to M. bovis prevalence and public health significance of BTB in Cameroon were assessed. Slaughter inspection records from major cities revealed that BTB detection rates in cattle from 0.18% to 4.25% and BTB lesions were most common. Analyses of tissues and sera confirmed BTB in 31% (Ziehl-Neelsen), 51% (culture), and 60% (antibody detection) of test cattle. Among c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 32 publications
10
39
5
Order By: Relevance
“…For example, it was not uncommon to note questionable summary meat inspection reports when compared to the crude abattoir registers. Poor clinical meat inspection records, which could not be relied upon, have been reported in Cameroon (Awah-Ndukum et al 2005;Awah-Ndukum et al 2010). The findings of this study agree with earlier reports that post mortem surveillance through the detection of bovine TB lesions depend on the work load, time and diligence of the inspector conducting the examination (Corner et al 1990;Edwards et al 1997;Shitaye et al 2006).…”
Section: Prevalence Of Bovine Tuberculosis Based On the Detection Of supporting
confidence: 82%
See 1 more Smart Citation
“…For example, it was not uncommon to note questionable summary meat inspection reports when compared to the crude abattoir registers. Poor clinical meat inspection records, which could not be relied upon, have been reported in Cameroon (Awah-Ndukum et al 2005;Awah-Ndukum et al 2010). The findings of this study agree with earlier reports that post mortem surveillance through the detection of bovine TB lesions depend on the work load, time and diligence of the inspector conducting the examination (Corner et al 1990;Edwards et al 1997;Shitaye et al 2006).…”
Section: Prevalence Of Bovine Tuberculosis Based On the Detection Of supporting
confidence: 82%
“…Mycobacteriological diagnosis of bovine TB in animals is practically unknown in Cameroon and the culture of human sputa is only sporadically performed and then mainly for research purposes. Awah-Ndukum et al (2010) reported acid-fast tubercle bacilli in 51% of suspected TB lesions in cattle based on mycobacterial culture and ZiehlNeelsen staining with microscopy and in 31% of the specimens based on direct smear microscopy with Ziehl-Neelsen staining without culture.…”
mentioning
confidence: 99%
“…In the present study, 58.1% of respondents have awareness about bovine TB; however only 30.8% of them had awareness on bovine TB as it is zoonotic. This report disagrees with report from Cameroon, which indicated 81.9% of cattle handlers know bovine TB, and 67.9% of them aware as bovine TB is zoonotic [14]. Study in in Shinile town, Somali regional state, eastern Ethiopia also indicates that majority (94.9%) of the respondents had, at the very least, heard of TB disease [15].…”
Section: Discussioncontrasting
confidence: 55%
“…Only 14% of cattle owners interviewed understood that BTb is zoonotic, while 70% of the respondent did not know that cattle could have Tb. This agrees with report from Cameroon, which indicated 81.9% of cattle handlers know BTb; however, with 67.9% of them know BTb is zoonotic [26].…”
Section: Discussionsupporting
confidence: 81%